2022
DOI: 10.1055/s-0042-1756369
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality of Electronic Medical Record Documentation: Development of a Compliance and Quality Program

Abstract: Background Introducing an electronic medical record (EMR) system into a complex health care environment fundamentally changes clinical workflows and documentation processes and, hence, has implications for patient safety. After a multisite “big-bang” EMR implementation across our large public health care organization, a quality improvement program was developed and implemented to monitor clinician adoption, documentation quality, and compliance with workflows to support high-quality patient care. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Similar studies have demonstrated improvements in workflow in other clinical settings, and support the need for ongoing QI and optimization programs for improved patient care. [9][10][11] The key to the improvements seen in this study stem from the close relationship between EHR interventions and clinical workflow. When collecting baseline data, detailed evaluation and analysis of clinician workflow, perceived inefficiencies, and user feedback were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have demonstrated improvements in workflow in other clinical settings, and support the need for ongoing QI and optimization programs for improved patient care. [9][10][11] The key to the improvements seen in this study stem from the close relationship between EHR interventions and clinical workflow. When collecting baseline data, detailed evaluation and analysis of clinician workflow, perceived inefficiencies, and user feedback were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…We established the definitions for each clinical data life cycle stage by reviewing the literature (Table 2). The literature included in the review often describes the data life cycle for improving hospital EHR quality, quality measurement, and clinical decision support [29][30][31][32][33].…”
Section: Data Quality Assessment Framework Based On Clinical Data Lif...mentioning
confidence: 99%
“…In our literature review, we found one commonality: all stages are interrelated and emphasize the need to manage data from a holistic, life cycle perspective [23]. The Plan-Do-Study-Act (PDSA) cycle, which was frequently mentioned in most of the articles we reviewed, is primarily used for short-term processes, such as data construction or operation [30,36,37]. Therefore, the PDSA cycle, which is mainly used in the data construction stage, could not be applied in our study.…”
Section: Proposed Data Framework Based On Clinical Data Life Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…One benefit of having an EMR system that collects data on patient care is that this data can be collated and presented back to the user for action if needed. Accordingly, where available, EMR data dashboards have been used to provide feedback and track selected quality care indicators and metrics over time (3). Benefits of ongoing scheduled data collections and display include identification of care gaps for system response and assurance of continued adherence to and/or meeting of quality standards.…”
mentioning
confidence: 99%